105 IgG4-Related Disease of the Esophagus: A Case Report and Review of Literature. (11th January 2018) - Sharma, Divya; Mann, Steven; Lin, Jingmei; Cummings, Oscar
Abstract: Objectives: IgG4-related disease is recognized as a fibro-inflammatory condition characterized by tendency to form tumefactive lesions, characteristic histopathologic appearance, and often but not always elevated serum IgG4 concentrations. IgG4-related disease involving the esophagus is extremely rare, with only four cases reported thus far. Methods: We describe IgG4-related disease of the esophagus in an 18-year-old man who presented with unexplained progressive dysphagia and weight loss of two-year duration. The barium fluoro esophagogram revealed prominent stricture involving distal 7–8 cm of the esophagus. Inability to dilate the stricture led to esophagectomy. Results: The esophageal resection specimen showed a dense transmural lymphoplasmacytic infiltrate with a predominance of IgG4-positive plasma cells, focal storiform fibrosis, and non-obliterative phlebitis. Once the suspicion of IgG4-related disease involving the esophagus was raised, clinical correlation with an elevated serum IgG4 level was made. The patient was started on steroids and had an uneventful postoperative period. Conclusion: We herein report a rare case of IgG4-related disease of the esophagus and present the review of literature emphasizing potential pitfalls in diagnosis of this rare condition.